Study of Magnetic Field and Rotation on Couple-Stress in Non-Newtonian Fluids (International Journal of Scientific Research in Science and Technology, 2025)
In this present paper, we studied about magnetic field and rotation on couple-stress in a non-Newtonian fluids.